Composite hydrogen-resistant coating for hydrogen conveying pipeline and preparation process of composite hydrogen-resistant coating
By applying a composite hydrogen-resistance coating structure on the hydrogen transport pipeline, including a nickel-plated alloy layer, a magnetic nanocomposite layer and a hydrogen isolation layer, the problems of prone to cracking and complex preparation processes of existing coatings are solved, and efficient hydrogen barrier is achieved and the corrosion resistance of the pipes extend the service life.
Patent Information
- Application Number
- CN202411248662.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-20
AI Technical Summary
The existing hydrogen transmission pipeline hydrogen-resistance coating is prone to cracking and peeling under high pressure environments, and the preparation process is complex and expensive, and it is difficult to apply on a large scale, so it cannot effectively solve the problems of hydrogen embrittlement and hydrogen permeation.
Using composite hydrogen-retardant coating structure, including carbon steel pipe nickel-plated alloy layer, magnetic nanocomposite layer, hydrogen insulation layer and inner layer protective layer, it is prepared by electroplating and ultrasonic mixing to ensure the thickness and adhesion of each layer and reduce the Hydrogen permeation and corrosion.
It achieves a hydrogen resistance effect with strong durability and good stability, reduces the risk of hydrogen embrittlement, improves the wear resistance and adhesion of the pipeline, extends the service life, and facilitates timely replacement of the pipeline through inspection.
Smart Images

Figure SMS_5
Abstract
Description
Technical Field
[0001] The present invention relates to a technical field related to the field of hydrogen barrier technology for hydrogen transmission pipelines, and in particular to a composite hydrogen barrier coating for hydrogen transmission pipelines and a preparation process thereof. Background Art
[0002] At present, my country's hydrogen energy industry is entering the fast lane of development. The demand for hydrogen in urban areas will continue to increase. It is expected that by 2050, hydrogen energy will become an important part of the energy structure. However, the source of hydrogen is not evenly distributed, which requires hydrogen to be transported to the corresponding areas. Among the many ways of hydrogen energy transportation, the use of pipelines for hydrogen transportation and dynamic storage is the best way to solve the distributed, dynamic, safe and economical storage and transportation of hydrogen energy. However, under high-pressure environmental conditions, hydrogen molecules can produce adsorbed hydrogen atoms on the surface of pipeline steel by the mechanism of dissociation and adsorption, and enter the steel, causing hydrogen embrittlement or other hydrogen-induced failure forms, endangering the safe operation of the pipeline. Due to the flammable and explosive characteristics of hydrogen, the service safety issues of hydrogen pipelines will be more prominent than those of traditional oil and gas pipelines.
[0003] Pipeline steel is a common material for hydrogen pipelines, and common ones include X42, X52, X56, X70, X80, etc. Covering its surface with a coating that delays hydrogen penetration is one of the important means to solve the hydrogen embrittlement problem of steel. The design of coatings that delay hydrogen penetration mainly considers two aspects. On the one hand, a coating with low porosity and high density is prepared to block the entry of hydrogen; on the other hand, multiple hydrogen traps are created to capture hydrogen atoms, thereby reducing the concentration of free hydrogen that can diffuse in the material.
[0004] An effective way to solve the problems of hydrogen embrittlement and hydrogen permeation is to treat the pipeline surface and form a protective film on the inner surface that hinders hydrogen penetration, namely a hydrogen barrier coating. Currently, common hydrogen barrier coatings are mainly divided into two categories: non-oxide coatings and oxide coatings. Non-oxide coatings mainly include TiC, TiN, SiC, etc., and oxide coatings mainly include Al2O3, Cr2O3, Y2O3, etc. However, in the actual application of hydrogen pipelines, existing hydrogen barrier coatings still have many problems: there is often a large difference in the thermal expansion coefficient between the non-oxide coating and the steel substrate, and the risk of cracking and peeling of the coating increases significantly with the increase of coating thickness; although the oxide coating has excellent hydrogen permeation resistance, its preparation method has certain limitations, is expensive, and has a complex process. Most of them are only suitable for the research of small laboratory components and are difficult to be applied on a large scale in hydrogen pipelines. Summary of the invention
[0005] In view of the above shortcomings, the present invention aims to provide a hydrogen barrier coating having good hydrogen barrier effect, strong durability, good stability, and not prone to cracking and peeling, and a preparation process thereof. The technical solution of the present invention is as follows:
[0006] A composite hydrogen barrier coating for a hydrogen pipeline comprises a composite base layer, a magnetic nano-composite layer, a hydrogen isolation layer and an inner protective layer which are sequentially arranged on the inner wall of the hydrogen pipeline, wherein the surface of the composite base layer comprises a carbon steel pipeline nickel-plated alloy layer, the carbon steel pipeline nickel-plated alloy layer is covered with a magnetic nano-composite layer, and the magnetic nano-composite layer comprises nano-magnetic powder, nano-carbon tubes, elastic modified materials and a coupling agent; the hydrogen isolation layer is a polyurethane nano-ceramic composite layer, and the protective layer is a composite coating of polytetrafluoroethylene and graphite.
[0007] Furthermore, the thickness of the nickel alloy layer of the carbon steel pipe is 15 to 20 μm, and the electroplating solution formula of the nickel alloy layer is 120-200 g / L nickel sulfate NiSO4, 30-60 g / L ferric chloride FeCl3, 0.1 to 0.5 g / L brightener ethyl phthalate and stabilizer ammonia water, and the pH value is adjusted to 4.8 to 5.3 by ammonia water.
[0008] Furthermore, the thickness of the magnetic nano-composite layer is 80 to 150 microns, and the nano-magnetic powder includes 30 to 40 parts of nano-magnetite Fe3O4, 15 to 25 parts of nano-iron tungstate FeWO4, 10 to 20 parts of nano-cobalt ferrite CoFe2O4 and 5 to 15 parts of nano-iron oxide Fe2O3 by mass fraction; 5 to 15 parts of nano-carbon tubes; 2 to 5 parts of polyurethane rubber (PU) and 2 to 5 parts of ethylene-vinyl acetate EVA, and 0.5 to 2 parts of silane coupling agent APTES as elastic modified materials.
[0009] Furthermore, the particle sizes of the nano magnetite Fe3O4, nano iron tungstate FeWO4, nano cobalt ferrite CoFe2O3 and nano iron oxide Fe2O3 are 10 to 20 nm, and the diameter of the nano carbon tubes is 1.5 to 2 nm.
[0010] Furthermore, the polyurethane nano-ceramic composite layer includes 100-120 parts by weight of polyurethane resin, 15-20 parts by weight of nano-ceramic particles, 10-15 parts by weight of epoxy resin, 2-4 parts by weight of dispersant polyvinylpyrrolidone PVP, 0.5-1 parts by weight of catalyst dibutyltin dilaurate DBTL, and 60-80 parts by weight of solvent acetone.
[0011] Furthermore, the polyurethane resin is a polyester polyurethane prepolymer.
[0012] Furthermore, the nano ceramic particles are a mixture of one or more of aluminum oxide Al2O3, silicon nitride Si3N4, boron nitride BN, silicon carbide SiC and zirconium oxide ZrO2.
[0013] Furthermore, the polyurethane nano-ceramic composite layer has a thickness of 200 to 400 microns.
[0014] Furthermore, the mass ratio of graphite to PTFE in the protective layer is 1:2-3, the solvent is hydrofluoroether HFE, and the thickness of the protective layer is 20-40 microns.
[0015] Furthermore, a preparation process of a composite hydrogen barrier coating for a hydrogen transmission pipeline is characterized by comprising the following steps:
[0016] S1. Material preparation
[0017] Carbon steel pipes, nickel alloy electroplating solution, nano magnetic powder (nano magnetite, nano iron tungstate, nano cobalt ferrite, nano iron oxide), nano carbon tubes, polyurethane rubber (PU), ethylene vinyl acetate EVA, polyurethane resin, nano ceramic particles (alumina, silicon nitride, etc.), epoxy resin, dispersant (PVP), catalyst (DBTL), solvent (acetone), polytetrafluoroethylene (PTFE), graphite;
[0018] S2. Nickel alloy plating
[0019] Prepare the carbon steel pipeline in advance, heat the steel pipe to eliminate stress, cool it to room temperature, clean the surface of the carbon steel pipeline, remove oil and rust, prepare the nickel alloy plating solution according to the formula, mix nickel sulfate, ferric chloride, brightener and stabilizer, use water as solvent to obtain the nickel alloy plating solution, electroplate the pipeline in the nickel alloy plating solution, control the plating thickness to 15-20 μm, then rinse the plating surface with deionized water to remove the residual plating solution, and perform sandblasting passivation treatment on the plating layer to further improve the corrosion resistance and wear resistance;
[0020] S3. Preparation of magnetic nanocomposite layer
[0021] Prepare a magnetic nano composite material coating, mix nano magnetite Fe3O4, nano iron tungstate FeWO4, nano cobalt ferrite CoFe2O4, nano iron oxide Fe2O3, nano carbon tubes, polyurethane rubber (PU), and ethylene vinyl acetate (EVA) according to a formula, add deionized water and ultrasonically mix to form a coating, evenly coat the composite material coating on the nickel alloy layer on the inner wall of the pipeline, dry with hot air at 60 to 80°C, heat and cure at a curing temperature of 120 to 180°C, and generally cure for 1 to 2 hours, slowly cool to room temperature after curing, grind and polish to ensure a thickness of 80 to 150 microns, and further perform a sandblasting passivation treatment to improve corrosion resistance and adhesion;
[0022] S4. Preparation of polyurethane nano-ceramic composite layer
[0023] Prepare a polyurethane nano-ceramic composite material, mix polyurethane resin, nano-ceramic particles, epoxy resin, PVP, DBTL and acetone according to a mass ratio, mix them evenly by ultrasonic mixing to form a coating, apply the mixture on the magnetic nano-composite layer, control the wet film thickness to 200-400 microns, dry at 70-80° C., cure at 150-180° C. for 1-2 hours, slowly cool to room temperature after curing, grind and polish to ensure uniformity, and sandblast to passivate the surface of the polyurethane nano-ceramic composite layer;
[0024] S5. Coating inner protective layer
[0025] Prepare a composite coating of polytetrafluoroethylene and graphite, mix them in a solvent hydrofluoroether (HFE) according to a mass ratio, mix them evenly by ultrasonic mixing to form a coating, apply a protective layer on the hydrogen isolation layer, dry them naturally at room temperature for 1 to 2 hours, cure them at 60 to 100° C., cool them to room temperature, grind and polish them, and control the thickness of the composite coating to be 20 to 40 μm;
[0026] S6. Pipeline inspection
[0027] The properties of the obtained pipeline are tested.
[0028] Beneficial effects:
[0029] 1. The nickel-plated alloy layer of the present invention provides additional anti-corrosion protection, and at the same time has a thermal expansion coefficient similar to that of the carbon steel pipeline, which reduces cracking caused by temperature changes. Combined with the magnetic nano-composite layer, it effectively reduces the erosion of hydrogen on carbon steel; 2. The hydrogen isolation layer of the present invention combines the advantages of polymers and nano-ceramics, has good toughness and high strength, effectively prevents the penetration of hydrogen, and reduces the risk of hydrogen embrittlement; 3. The magnetic nano-composite layer of the present invention can improve the wear resistance and adhesion of the pipeline, and at the same time provide a detection method for hydrogen penetration. Detecting hydrogen penetration facilitates timely replacement of the pipeline; 4. The inner protective layer of the present invention is resistant to high temperatures and provides additional thermal stability. Through the composite of PTFE and oxide, it has excellent lubricity and wear resistance, reduces pipeline friction, and extends service life; 5. Each layer of the present invention specifically has a certain toughness, which can effectively reduce the cracking problem that may occur due to temperature and pressure changes. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The present invention is implemented by the following steps
[0032] Example 1
[0033] S1. Material preparation
[0034] The material specifications of the embodiment of the present invention are as follows:
[0035] Carbon steel pipe (specification model ASTM A106, Φ400mm×600cm, wall thickness 15mm), nickel alloy plating solution, nano magnetic powder (nano magnetite with a particle size of 10-20nm, nano iron tungstate, nano cobalt ferrite, nano iron oxide), nano carbon tube (diameter 1.5-2nm), polyurethane rubber PU (BASF 1185A), ethylene vinyl acetate EVA (DuPont 4205), polyurethane resin ( 5700), nano ceramic particles (alumina, silicon nitride, etc.), epoxy resin ( 1001F), dispersant (PVP), catalyst (DBTL), solvent (acetone), polytetrafluoroethylene (PTFE), graphite (high-purity natural graphite powder between 10 and 20 microns, screened by a vibrating screen or a standard sieve); the reagents not limited in the types of the present invention are all conventional reagents purchased from the market, and the reagents with requirements on particle size and diameter are screened out by those skilled in the art using conventional reagents according to the properties of the substances through relevant conventional screening methods. The different particle size distributions caused by different methods do not affect the expression of the overall properties in the present invention.
[0036] S2. Nickel alloy plating
[0037] Prepare the carbon steel pipeline in advance, heat the steel pipe to eliminate stress, cool it to room temperature, clean the surface of the carbon steel pipeline, remove oil and rust, and prepare the nickel alloy plating liquid according to the formula. The solvent is water and the concentration is 12g / L nickel sulfate NiSO 4 , 30g / L ferric chloride FeCl 3 , 0.1g / L brightener ethyl phthalate, adjust the pH value to 4.8-5.3 with ammonia water, electroplate the pipe in the nickel alloy plating solution through the electroplating process, and control the plating thickness to 15μm. Then, rinse the plating surface with deionized water to remove the residual plating solution, and perform sandblasting passivation on the plating to further improve the corrosion resistance and wear resistance;
[0038] S3. Preparation of magnetic nanocomposite layer
[0039] A magnetic nano composite material coating is prepared according to a formula, including 35 parts of nano magnetite Fe3O4, 20 parts of nano iron tungstate FeWO4, 15 parts of nano cobalt ferrite CoFe2O4 and 10 parts of nano iron oxide Fe2O3; 10 parts of nano carbon tubes; 3 parts of polyurethane rubber (PU) and 3 parts of ethylene-vinyl acetate EVA of elastic modified materials, and 1 part of silane coupling agent APTES, and then deionized water is added and ultrasonically mixed at a low frequency of 20kHz to 40kHz for 10 minutes to uniformly prepare the coating, and the composite material coating is uniformly coated on the nickel-plated alloy layer, hot air drying at 60 to 80°C, heating and curing, the curing temperature is 120 to 180°C, the curing time is usually 1 to 2 hours, and after curing, it is slowly cooled to room temperature, polished to ensure that the thickness is 100 microns, and then further sandblasted and passivated to improve corrosion resistance and adhesion.
[0040] S4. Preparation of polyurethane nano-ceramic composite layer
[0041] Prepare a polyurethane nano-ceramic composite material, including 100 parts of polyurethane resin, 15 parts of nano-ceramic particles, 10 parts of epoxy resin, 2 parts of dispersant polyvinyl pyrrolidone PVP, 0.5 parts of catalyst dibutyltin dilaurate DBTL, and 60 parts of solvent acetone, mix them evenly by low-frequency 20kHz to 40kHz ultrasonic mixing for 10 minutes to make a coating, apply the mixture on the magnetic nano-composite layer, dry at 70-80°C, cure at 150-180°C for 1-2 hours, slowly cool to room temperature after curing, grind and polish, control the thickness to 300 microns to ensure uniformity, and passivate the surface of the polyurethane nano-ceramic composite layer by sandblasting;
[0042] S5. Coating inner protective layer
[0043] Prepare a composite coating of polytetrafluoroethylene and graphite, mix them in a solvent hydrofluoroether (HFE) at a mass ratio of 2:1, mix them evenly by low-frequency 20kHz to 40kHz ultrasonic mixing for 10 minutes to make a coating, apply a protective layer on the hydrogen isolation layer, dry it naturally at room temperature for 1 to 2 hours, cure it at 60 to 100°C, cool it to room temperature, grind and polish it, and control the thickness to 20 microns;
[0044] S6. Pipeline inspection
[0045] The properties of the obtained pipeline are tested to confirm whether they meet the relevant standards.
[0046] Example 2
[0047] S2. Nickel alloy plating
[0048] Other conditions remain unchanged, and the second step S2. nickel alloy layer plating operation is adjusted.
[0049] Prepare the carbon steel pipeline in advance, heat the steel pipe to eliminate stress, cool it to room temperature, clean the surface of the carbon steel pipeline, remove oil and rust, prepare the nickel alloy plating solution according to the formula, the concentration is 200g / L nickel sulfate NiSO4, 60g / L ferric chloride FeCl3, 0.5g / L brightener ethyl phthalate, adjust the pH value to 4.8-5.3 with ammonia water, electroplate the pipeline in the nickel alloy plating solution through the electroplating process, and control the coating thickness to 20μm, then rinse the coating surface with deionized water to remove the residual electroplating solution, and perform sandblasting passivation treatment on the coating to further improve the corrosion resistance and wear resistance;
[0050] Example 3
[0051] S2. Nickel alloy plating
[0052] Other conditions remain unchanged, and the second step S2. nickel alloy layer plating operation is adjusted.
[0053] Prepare the carbon steel pipeline in advance, heat the steel pipe to eliminate stress, cool it to room temperature, clean the surface of the carbon steel pipeline, remove oil and rust, and prepare the nickel plating alloy liquid according to the formula with a concentration of 12g / L nickel sulfate NiSO 4 , 30g / L ferric chloride FeCl 3 , 0.1g / L brightener ethyl phthalate, adjust the pH value to 4.8-5.3 with ammonia water, electroplate the pipe in the nickel alloy plating solution through the electroplating process, and control the plating thickness to 15μm. Then, rinse the plating surface with deionized water to remove the residual plating solution, and perform sandblasting passivation on the plating to further improve the corrosion resistance and wear resistance;
[0054] Example 4
[0055] Other conditions remain unchanged, and the third step S3. Preparation of magnetic nanocomposite layer is adjusted.
[0056] A magnetic nano composite material coating is prepared according to a formula, including 30 parts of nano magnetite Fe3O4, 15 parts of nano iron tungstate FeWO4, 10 parts of nano cobalt ferrite CoFe2O4 and 5 parts of nano iron oxide Fe2O3; 5 parts of nano carbon tubes; 2 parts of polyurethane rubber (PU) and 2 parts of ethylene-vinyl acetate EVA of elastic modified materials, and 0.5 parts of silane coupling agent APTES, and then deionized water is added and ultrasonically mixed at a low frequency of 20kHz to 40kHz for 10 minutes to make a coating, and the composite material coating is evenly coated on the nickel-plated alloy layer, hot air drying at 60 to 80°C, heating and curing, the curing temperature is 120 to 180°C, the curing time is usually 1 to 2 hours, and after curing, it is slowly cooled to room temperature, polished to ensure that the thickness is 80 microns, and then further sandblasted and passivated to improve corrosion resistance and adhesion.
[0057] Example 5
[0058] Other conditions remain unchanged, and the third step S3. Preparation of magnetic nanocomposite layer is adjusted.
[0059] A magnetic nano composite material coating is prepared according to a formula, including 30 parts of nano magnetite Fe3O4, 15 parts of nano iron tungstate FeWO4, 10 parts of nano cobalt ferrite CoFe2O4 and 5 parts of nano iron oxide Fe2O3; 5 parts of nano carbon tubes; 2 parts of polyurethane rubber (PU) and 2 parts of ethylene-vinyl acetate EVA of elastic modified materials, and 0.5 parts of silane coupling agent APTES, and then deionized water is added and ultrasonically mixed at a low frequency of 20kHz to 40kHz for 10 minutes to uniformly prepare the coating, and the composite material coating is uniformly coated on the nickel-plated alloy layer, hot air drying at 60 to 80°C, heating and curing, the curing temperature is 120 to 180°C, the curing time is generally 1 to 2 hours, and after curing, it is slowly cooled to room temperature, polished to ensure that the thickness is 150 microns, and then further sandblasted and passivated to improve corrosion resistance and adhesion.
[0060] Example 6
[0061] Other conditions remain unchanged, and the third step S3. Preparation of magnetic nanocomposite layer is adjusted.
[0062] A magnetic nano composite material coating is prepared according to a formula, including 40 parts of nano magnetite Fe3O4, 25 parts of nano iron tungstate FeWO4, 20 parts of nano cobalt ferrite CoFe2O4 and 15 parts of nano iron oxide Fe2O3; 15 parts of nano carbon tubes; 5 parts of elastic modified materials polyurethane rubber (PU) and 5 parts of ethylene-vinyl acetate EVA, 2 parts of silane coupling agent APTES, and then deionized water is added and ultrasonically mixed at a low frequency of 20kHz to 40kHz for 10 minutes to make a coating, and the composite material coating is evenly coated on the nickel-plated alloy layer, hot air drying at 60 to 80°C, heating and curing, the curing temperature is 120 to 180°C, the curing time is usually 1 to 2 hours, and after curing, it is slowly cooled to room temperature, polished to ensure that the thickness is 100 microns, and then further sandblasted and passivated to improve corrosion resistance and adhesion.
[0063] Example 7
[0064] Other conditions remain unchanged, and the fourth step S4. Preparation of polyurethane nano-ceramic composite layer is adjusted.
[0065] Prepare a polyurethane nano-ceramic composite material, including 120 parts of polyurethane resin, 20 parts of nano-ceramic particles, 15 parts of epoxy resin, 4 parts of dispersant polyvinyl pyrrolidone PVP, 1 part of catalyst dibutyltin dilaurate DBTL, and 80 parts of solvent acetone, mix them evenly by low-frequency 20kHz to 40kHz ultrasonic mixing for 10 minutes to make a coating, apply the mixture on the magnetic nano-composite layer, dry at 70-80°C, cure at 150-180°C for 1-2h, slowly cool to room temperature after curing, grind and polish, control the thickness to 200 microns to ensure uniformity, and passivate the surface of the polyurethane nano-ceramic composite layer by sandblasting;
[0066] Example 8
[0067] Other conditions remain unchanged, and the fourth step S4. Preparation of polyurethane nano-ceramic composite layer is adjusted.
[0068] Prepare a polyurethane nano-ceramic composite material, including 120 parts of polyurethane resin, 20 parts of nano-ceramic particles, 15 parts of epoxy resin, 4 parts of dispersant polyvinyl pyrrolidone PVP, 1 part of catalyst dibutyltin dilaurate DBTL, and 80 parts of solvent acetone, mix them evenly by low-frequency 20kHz to 40kHz ultrasonic mixing for 10 minutes to make a coating, apply the mixture on the magnetic nano-composite layer, dry at 70-80°C, and cure at 150-180°C for 1-2h. After curing, slowly cool to room temperature, grind and polish, control the thickness to 400 microns to ensure uniformity, and passivate the surface of the polyurethane nano-ceramic composite layer by sandblasting.
[0069] Example 9
[0070] Adjustment of the fifth step S5. coating the inner protective layer
[0071] Prepare a composite coating of polytetrafluoroethylene and graphite, mix them in a solvent hydrofluoroether (HFE) at a mass ratio of 2:1, mix them evenly with low-frequency 20kHz to 40kHz ultrasonic mixing for 10 minutes to make a coating, apply a protective layer on the hydrogen isolation layer, dry it naturally at room temperature for 1 to 2 hours, cure it at 60 to 100°C, cool it to room temperature, grind and polish it, and control the thickness to 40 microns;
[0072] Example 10
[0073] Adjustment of the fifth step S5. coating the inner protective layer
[0074] Prepare a composite coating of polytetrafluoroethylene and graphite, mix them in a solvent hydrofluoroether (HFE) in a mass ratio of 3:1, mix them evenly by low-frequency 20kHz to 40kHz ultrasonic mixing for 10 minutes to make a coating, apply a protective layer on the hydrogen insulation layer, dry it naturally at room temperature for 1 to 2 hours, cure it at 60 to 100°C, cool it to room temperature, grind and polish it, and control the thickness to 20 microns.
[0075] The hydrogen permeability of the coated metal substrate was tested by electrochemical workstation after immersion in 3.5wt% NaCl solution for 90 days. The test standard is GB / T 23409.
[0076]
[0077] After testing, it was found that the different types of pipelines obtained by the implementation methods of the present invention all have low hydrogen permeability and good hydrogen barrier effect. At the same time, the hydrogen pipelines have excellent corrosion resistance.
[0078] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0079] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A composite hydrogen barrier coating for a hydrogen transmission pipeline, characterized in that: It comprises a composite base layer, a magnetic nano-composite layer, a hydrogen isolation layer and an inner protective layer which are sequentially arranged on the inner wall of the hydrogen transmission pipeline. The surface of the composite base layer comprises a carbon steel pipeline nickel-plated alloy layer, and the carbon steel pipeline nickel-plated alloy layer is covered with a magnetic nano-composite layer. The magnetic nano-composite layer comprises nano-magnetic powder, nano-carbon tubes, elastic modified materials and coupling agents. The hydrogen isolation layer is a polyurethane nano-ceramic composite layer, and the protective layer is a composite coating of polytetrafluoroethylene and graphite.
2. The composite hydrogen barrier coating for a hydrogen transport pipeline according to claim 1, characterized in that: The thickness of the nickel alloy layer of the carbon steel pipeline is 15-20 μm, and the electroplating solution formula of the nickel alloy layer is 120-200 g / L nickel sulfate NiSO4, 30-60 g / L ferric chloride FeCl3, 0.1-0.5 g / L brightener ethyl phthalate and stabilizer ammonia water, and the pH value is adjusted to 4.8-5.3 by ammonia water.
3. The composite hydrogen barrier coating for a hydrogen transport pipeline according to claim 1, characterized in that: The thickness of the magnetic nanocomposite layer is 80 to 150 microns, and the nanomagnetic powder includes 30 to 40 parts of nanomagnetite Fe3O4, 15 to 25 parts of nano iron tungstate FeWO4, 10 to 20 parts of nano cobalt ferrite CoFe2O4 and 5 to 15 parts of nano iron oxide Fe2O4 by mass fraction. 3; 5-15 parts of nano carbon tubes; 2-5 parts of polyurethane rubber (PU) and 2-5 parts of ethylene vinyl acetate EVA as elastic modifying materials, and 0.5-2 parts of silane coupling agent APTES.
4. The composite hydrogen barrier coating for a hydrogen transmission pipeline according to claim 3, characterized in that: The particle sizes of the nano magnetite Fe3O4, nano iron tungstate FeWO4, nano cobalt ferrite CoFe2O3 and nano iron oxide Fe2O3 are 10-20nm, and the diameter of the nano carbon tube is 1.5-2nm.
5. The composite hydrogen barrier coating for a hydrogen transmission pipeline according to claim 1, characterized in that: The polyurethane nano-ceramic composite layer comprises 100-120 parts of polyurethane resin, 15-20 parts of nano-ceramic particles, 10-15 parts of epoxy resin, 2-4 parts of dispersant polyvinylpyrrolidone PVP, 0.5-1 part of catalyst dibutyltin dilaurate DBTL, and 60-80 parts of solvent acetone.
6. The composite hydrogen barrier coating for a hydrogen transport pipeline according to claim 5, characterized in that: The polyurethane resin is a polyester polyurethane prepolymer.
7. The composite hydrogen barrier coating for a hydrogen transport pipeline according to claim 5, characterized in that: The nano ceramic particles are a mixture of one or more of aluminum oxide Al2O3, silicon nitride Si3N4, boron nitride BN, silicon carbide SiC and zirconium oxide ZrO2.
8. The composite hydrogen barrier coating for a hydrogen transport pipeline according to claim 7, characterized in that: The thickness of the polyurethane nano-ceramic composite layer is 200 to 400 microns.
9. The composite hydrogen barrier coating for a hydrogen transport pipeline according to claim 1, characterized in that: The mass ratio of graphite to PTFE in the protective layer is 1:2-3, the solvent is hydrofluoroether HFE, and the thickness of the protective layer is 20-40 microns.
10. The process for preparing a composite hydrogen barrier coating for a hydrogen pipeline according to claim 1, characterized in that The following steps are involved: S1. Material preparation Carbon steel pipes, nickel alloy electroplating solution, nano magnetic powder (nano magnetite, nano iron tungstate, nano cobalt ferrite, nano iron oxide), nano carbon tubes, polyurethane rubber (PU), ethylene vinyl acetate EVA, polyurethane resin, nano ceramic particles (alumina, silicon nitride, etc.), epoxy resin, dispersant (PVP), catalyst (DBTL), solvent (acetone), polytetrafluoroethylene (PTFE), graphite; S2. Nickel alloy plating Prepare the carbon steel pipeline in advance, heat the steel pipe to eliminate stress, cool it to room temperature, clean the surface of the carbon steel pipeline, remove oil and rust, prepare the nickel alloy plating solution according to the formula, mix nickel sulfate, ferric chloride, brightener and stabilizer, use water as solvent to obtain the nickel alloy plating solution, electroplate the pipeline in the nickel alloy plating solution, control the plating thickness to 15-20 μm, then rinse the plating surface with deionized water to remove the residual plating solution, and perform sandblasting passivation treatment on the plating layer to further improve the corrosion resistance and wear resistance; S3. Preparation of magnetic nanocomposite layer Prepare a magnetic nano composite material coating, mix nano magnetite Fe3O4, nano iron tungstate FeWO4, nano cobalt ferrite CoFe2O4, nano iron oxide Fe2O3, nano carbon tubes, polyurethane rubber (PU), and ethylene vinyl acetate (EVA) according to a formula, add deionized water and ultrasonically mix to form a coating, evenly coat the composite material coating on the nickel alloy layer on the inner wall of the pipeline, dry with hot air at 60 to 80°C, heat and cure at a curing temperature of 120 to 180°C, and generally cure for 1 to 2 hours, slowly cool to room temperature after curing, grind and polish to ensure a thickness of 80 to 150 microns, and further perform a sandblasting passivation treatment to improve corrosion resistance and adhesion; S4. Preparation of polyurethane nano-ceramic composite layer Prepare a polyurethane nano-ceramic composite material, mix polyurethane resin, nano-ceramic particles, epoxy resin, PVP, DBTL and acetone according to a mass ratio, mix them evenly by ultrasonic mixing to form a coating, apply the mixture on the magnetic nano-composite layer, control the wet film thickness to 200-400 microns, dry at 70-80° C., cure at 150-180° C. for 1-2 hours, slowly cool to room temperature after curing, grind and polish to ensure uniformity, and sandblast to passivate the surface of the polyurethane nano-ceramic composite layer; S5. Coating inner protective layer Prepare a composite coating of polytetrafluoroethylene and graphite, mix them in a solvent hydrofluoroether (HFE) according to a mass ratio, mix them evenly by ultrasonic mixing to form a coating, apply a protective layer on the hydrogen isolation layer, dry them naturally at room temperature for 1 to 2 hours, cure them at 60 to 100° C., cool them to room temperature, grind and polish them, and control the thickness of the composite coating to be 20 to 40 μm; S6. Pipeline inspection The properties of the obtained pipeline are tested.
Citation Information
Cited By
Method for electroplating Ni-P-Fe2O3-PTFE composite lubricating layer on surface of aluminum nitride substrate
CN121802410A
